Alcoholic Hepatitis versus Non-alcoholic Steatohepatitis: Levels of Expression of Some Proteins Involved in Tumorigenesis - Nguyen, Luan (Exp Mol Pathol, 2018)
Non-alcoholic steatohepatitis (NASH) is commonly associated with obesity, type 2 diabetes, and/or hypertriglyceridemia, while alcoholic steatohepatitis (ASH) is associated with alcohol abuse. Both NASH and ASH patients can develop cirrhosis and hepatocellular carcinoma (HCC) if left untreated. However, the rate of tumorigenesis in NASH and ASH appears to be different. Individuals with NAS H progress to HCC at a rate of 0.5% annually (Lindenmeyer et al., 2017), when individuals with ASH progress to HCC at a rate of 3–10% annually (Schwartz et al., 2012). Thus, the objective of our study is to determine if there are differences in NASH versus ASH in the levels of different proteins expressed involved in cancer development. The method used was measuring the proteins expressed in liver biopsied sections from NASH and ASH patients using immunohistochemical staining with fluorescent ant ibodies and then quantitating the fluorescence intensity morphometrically. The 20 proteins tested are parts of the Ingenuity Canonical Pathway of Molecular Mechanisms of Cancer and include: RAP2B, NAIP, FYN, PAK6, SUV39H1, GNAI1, BAX, E2F3, CKDN2B, BAK1, BCL2, DIABLO, RASGRF2, GNA15, PIK3CB, BRCA1, MAP2K1, BIRC3, CDK2, and ATM. In ASH, the proteins that showed upregulated levels of expression were SUV39H1, E2F3, BCL2, BAK1, BIRC3, and GNAI1. In NASH, the proteins that showed upregulated levels of expression were BAK1 and GNAI1 and the protein that showed downregulated level of expression was BCL2. Additionally, levels of expression for SUV39H1, E2F3, BCL2, BAK1, BIRC3, and GNAI1 were significant upregulated in ASH compared to NASH. These results showed significant differences in ASH compared to normal liver, and significant differences in ASH compared to NASH. Thus, we conclude that there are more proteins involved in tumorigenesis in ASH compared to NASH and in ASH compared to normal liver, which is consistent with the known tumor development rate in ASH and NASH.